An annotated bibliography of materials on Thailand written and/or published in the Philippines - Chety, Sida; Picache, Ursula G. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1974)
This annotated bibliography includes classified and unclassified works - theses (undergraduate and graduate), dissertations, seminar and conference papers, investigation papers, articles in periodicals, and miscellaneous publications on Thailand which are produced and published in the Philippines and written by Thais, Filipinos, or other nationals in the Philippines. These are on different subject areas and cover the period from 1933 up to June 1973. Excluded, however, are articles from popular magazines and newspapers.
It is divided into two parts. Part One is the listing of thesis, dissertations, and investigation papers. Part Two is the listing of periodical articles, mimeographed papers, seminar and conference papers. Both Part One and Part Two are classified under broad subject areas. In some cases the broad subjects are divided further into small topics. Under each subject, entries are arranged alphabetically by author, with complete bibliographic data. Each entry is provided with an item number, from 1-466. This is the number referred to in the author and title indexes which have been provided to facilitate the location of specific items.
The entries for Thai authors in this bibliography are under their surnames followed by the first names. For those names with titles of nobility or titles of royalty, the titles follow the first names.
A historical background of the relations between the Philippines and Thailand is presented in Chapter II for a better understanding of this bibliography.
Typescript.
Vita.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Thailand--Bibliography.